Crystal structure of (E)-amino(2-(3-ethoxy-4-hydroxybenzylidene)hydrazineyl)methaniminium nitrate hemihydrate C10H16N5O5.5 - Jin Ze-Sen; Liu E.; Liu Xiao-Jing; Jian Fang-Fang; Liang Tongling (Zeitschrift für Kristallographie - New Crystal Structures)
C10H16N5O5.5, monoclinic, C2/c (no. 15), a = 17.7836(8) Å, b = 9.4796(4) Å, c = 15.8740(8) Å, β = 97.093(5)°, V = 2655.6(2) Å3, Z = 8, Rgt(F) = 0.0469, wRref(F2) = 0.1289, T = 170 K.